Self-Care, Disease Activity and Health-Related Quality of Life Among Patients with Inflammatory Bowel Disease - U, Lovén Wickman; P, Yngman-Uhlin; H, Hjortswang; GH, Frisman (Archives of Clinical and Biomedical Research, 2020)
Introduction: Self-care is needed for patients living with inflammatory bowel disease so that they can manage symptoms in the context of activities of daily living. The objective was to explore self-care in relation to disease activity and health-related quality of life in patients with inflammatory bowel disease. Methods: We used a cross-sectional exploratory design and a total of 234 patients with inflammatory bowel disease participated. Disease specific measurements was used as, a newly developed self-care questionnaire, Harvey Bradshaw Index, the Simple Clinical Colitis Activity Index and Short Health Scale. Results: The results revealed that patients reported a high frequency of self-care maintenance as medication adherence, diet adaptation, planning the day and avoiding activities, self-care monitoring in symptom recognition and self-care management in managing stress and managing sleep. Higher disease activity was related to higher self-care activity. Compared to patients with ulcerative colitis, those with Crohn’s disease planned their day to a higher degree when their bowel symptoms interfered with daily life. Disease activity and avoiding activities decreased their health-related quality of life. Conclusion: Self-care was positively associated to higher disease activity. Higher disease activity highlight self-care maintenance as planning the day and avoiding activities in daily life what in turn decrease health-related quality of life. Regular discussions on symptoms in relation to self-care is of great importance for patients to adjust their daily activities.